Understanding the effect of postharvest tomato temperatures on two toxigenic Alternaria spp. strains: growth, mycotoxins and cell‐wall integrity‐related gene expression. (30th August 2019) - da Cruz Cabral, Lucía; Rodríguez, Alicia; Delgado, Josué; Patriarca, Andrea
Abstract: BACKGROUND: Tomato fruit is susceptible to Alternaria spp. spoilage. Correct postharvest management is necessary to prevent mold growth and mycotoxin accumulation, temperature being one of the main factors associated with these problems. The effect of different postharvest temperatures (5, 12, 25, and 35 °C) on growth, mycotoxin production, and stress‐related gene expression by two Alternaria spp. was assessed. RESULTS: Growth rates decreased rapidly when temperature was higher than the optimum (25 °C), while a gradual reduction was detected at lower temperatures. Tenuazonic acid (TeA) was strongly synthesized at all the temperatures that were evaluated, with a maximum between 12 and 25 °C. Alternariol monomethyl ether (AME) was produced only at the two lowest temperatures, with a peak at 12 °C. Regarding the expression of the stress‐related RHO1 gene, during active fungal growth both Alternaria spp. showed more copies of the gene as temperature increased. At the stationary phase, RHO1 gene expression was significantly higher at 12 °C, coinciding with the highest accumulation of AME. CONCLUSION: Changes in temperature related to different postharvest stages of tomato fruits markedly affect toxigenic Alternaria spp. The highest levels of both mycotoxins were recorded at 12 °C, a common storage temperature for tomato fruit. An association between alternariol biosynthesis and the cell wall integrity pathway was also noticed in relation to temperature, suggesting that temperature may act as a stressor stimulating the RHO1 gene expression, which in turn triggers this mycotoxin synthesis. These results will be useful in developing new strategies to control Alternaria spoilage efficiently in tomato fruit and by‐products. © 2019 Society of Chemical Industry